Some Rare and Threatened Plants of Sitamata Wildlife Sanctuary, Rajasthan - Jain, Anita; Katewa, S. S.; Galav, P. K. (Indian Forester, 2010)
The present study has been carried out in Sitamata Wildlife Sanctuary which is situated in Chittorgarh and Udaipur district of Southern region of Rajasthan. An extensive field survey of the study area was carried out during the year 2002-05. It reveals large number of threatened species, occurring wild in various habitats of the Sanctuary. A list of 39 rare and threatened plant species belonging to 36 genera and 24 families have been reported along with their local name, family, ecology, populationandthei present status.